Ossified uncertain malignant potential gastric glomus tumor with tumor thrombus - Irem Guvendir; Itır Ebru Zemheri; Kamile Altundal; Kamil Ozdil; Resul Kahraman; Ilkay Tosun (Wolters Kluwer Medknow Publications, 2021)
Glomus tumor is a rare mesenchymal tumor composed of perivascular glomus bodies. The most common presentation area of these tumors is peripheral soft tissue, particularly in the distal part of extremities. They rarely can occur in the gastrointestinal tract and the most common location is the stomach. Preoperative diagnosis of this tumor can be difficult because of rarity and overlapping features with other mesenchymal lesions with regard to clinical and pathological findings. Therefore, to exclude differential diagnosis and make a definitive diagnosis is possible only with histopathological examination. In this case, we evaluated glomus tumor of stomach according to 2019 WHO Digestive System Tumors and accurate diagnosed was Uncertain Malignant Potential Gastric Glomus Tumor.